2010
DOI: 10.1002/chir.20857
|View full text |Cite
|
Sign up to set email alerts
|

A significant role for high‐energy transitions in the ultraviolet circular dichroism spectra of polypeptides and proteins

Abstract: The nπ* and ππ* transitions of polypeptides mix significantly with very high energy transitions in the poly(Pro)II conformation, as evidenced by the strongly nonconservative CD spectrum in the 170-250 nm region. Because of this, the exciton model, the standard quantum mechanical model for predicting absorption and CD spectra of polypeptides, gives poor results for the poly(Pro) II (P(II)) conformation, although it works well for the α-helix, β-sheet, and β-turns. The exciton theory has been extended to include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
(92 reference statements)
1
9
0
1
Order By: Relevance
“…These spectral features are diagnostic of a very stable left-handed PPII helix conformation which is the conformation adopted in aqueous solution by PLP homopolypeptide. [33][34][35][36] In TBS solution at 0 C the CD spectrum shows a strong negative band at 205 nm and a weak positive band at 229 nm (Fig. 3B).…”
Section: Far-uv Circular Dichroism (Cd) Spectroscopymentioning
confidence: 93%
“…These spectral features are diagnostic of a very stable left-handed PPII helix conformation which is the conformation adopted in aqueous solution by PLP homopolypeptide. [33][34][35][36] In TBS solution at 0 C the CD spectrum shows a strong negative band at 205 nm and a weak positive band at 229 nm (Fig. 3B).…”
Section: Far-uv Circular Dichroism (Cd) Spectroscopymentioning
confidence: 93%
“…11 Although the TK assignment met with initial skepticism, 12 a further evaluation concluded that a range of studies now furnished ''strong evidence in favor of (this) proposal'' 13 and much subsequent research has supported this conclusion [14][15][16][17][18] including recent extended exciton-based theoretical CD studies. 19,20 Despite this consensus, two significant structural issues still remain to be clarified: the number of consecutive PPII conformations in a peptide sequence and the source of its relative stability. With respect to the first issue, two opinions have emerged.…”
Section: Introduction Wmentioning
confidence: 99%
“…The peptide bond π→π* transitions have been characterized to a limited extent, as have been the transitions of the different isolated side chain chromophores. 1–13 However, there has been little attention paid to the potential coupling of the peptide bond transitions to the side chain electronic transitions or to coupling between side chain transitions. Coupling of side chain – peptide bond transitions could be important in areas such as electron transport, for example.…”
Section: Introductionmentioning
confidence: 99%
“…There is little understanding of the electronic transitions of peptides and proteins. It is generally assumed that peptide and protein electronic transitions result from the summation of the electronic transitions of the constituent chromophores. The peptide bond π → π* transitions have been characterized to a limited extent, as have been the transitions of the different isolated side chain chromophores. However, there has been little attention paid to the potential coupling of the peptide bond transitions to the side chain electronic transitions or to coupling between side chain transitions. Coupling of side chain− peptide bond transitions could be important in areas such as electron transport, for example.…”
Section: Introductionmentioning
confidence: 99%